Pengembangan Kurikulum Pendidikan Islam dalam Perspektif Progresivisme - Mukh Nursikin (Institut Islam Nahdlatul Ulama Temanggung, 2020)
The consept of islam abaout liberation education indicates that every child owns elmentary potency and freedom as khalifah and ‘abid to explore the potency owned in solving life’s probelm. This research emphasizes on the methodological aspect of the development of Islamic education curriculum with in perspective progressivism. The aim of this research in to develop an islamic education curriculum by methodological design and approach in learning of islamic education concerming in perspective progressivism. To attain which is that aim, this research uses progressivism approach by learned contered design givingb a special place to the students. This study is a research, it is qualitative approach wit descriptive analysis as its method. The findings indicate that in practice, islamic education should refer to human being wxistence forming a democratic education mechanismn, opened, transformative, an interative, on the purpose of humanizing human beings, meaning that education is students to be able to develop their potency as Allah’s creation which funcition as khalifah mission and run the devation as intact person.